2020
DOI: 10.1093/ilar/ilaa029
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Marmoset Monkeys

Abstract: The use of the common marmoset monkey (Callithrix jacchus) for neuroscientific research has grown markedly in the last decade. Magnetic resonance imaging (MRI) has played a significant role in establishing the extent of comparability of marmoset brain architecture with the human brain and brains of other preclinical species (eg, macaques and rodents). As a non-invasive technique, MRI allows for the flexible acquisition of the same sequences across different species in vivo, including imaging of whole-brain fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 105 publications
(113 reference statements)
0
12
0
Order By: Relevance
“…Compared to isoflurane, sevoflurane does not have a pungent smell and is not irritating to the respiratory tract. Therefore, sevoflurane can be an alternative for mask induction with an induction chamber and maintenance of New World primates (such as marmosets) [ 118 ]. Previous PET studies of adult rhesus monkeys suggested sevoflurane exposure has minimal effect on cognitive function [ 119 ], and the suppression effects of sevoflurane on the BOLD signal and intrinsic neural activity of the human brain were seen [ 120 ].…”
Section: Effects Of Anesthesia On Cbf and Functional Connectivity Of ...mentioning
confidence: 99%
“…Compared to isoflurane, sevoflurane does not have a pungent smell and is not irritating to the respiratory tract. Therefore, sevoflurane can be an alternative for mask induction with an induction chamber and maintenance of New World primates (such as marmosets) [ 118 ]. Previous PET studies of adult rhesus monkeys suggested sevoflurane exposure has minimal effect on cognitive function [ 119 ], and the suppression effects of sevoflurane on the BOLD signal and intrinsic neural activity of the human brain were seen [ 120 ].…”
Section: Effects Of Anesthesia On Cbf and Functional Connectivity Of ...mentioning
confidence: 99%
“…One possible reason for not using fMRI in marmosets is that it is necessary to have a wide-bore MRI scanner for small animals to replicate currently published methods. In small animal MRI, the bore size in marmosets ranges from 15 to 30 cm without a gradient coil (Schaeffer et al, 2020a). An MRI with a small bore has advantages such as lower costs and a higher potential to equip high gradients than an MRI with a wide bore.…”
Section: Introductionmentioning
confidence: 99%
“…Small-bore MRI is also sufficient if the animals are under anesthesia. However, introducing a marmoset holder for fMRI is challenging to apply to small-bore MRI scanners (Schaeffer et al, 2020a). Therefore, if the development of a marmoset holder for small-bore MRI scanners were possible, the opportunities to conduct fMRI in marmosets would expand.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, marmosets have been more frequently used in preclinical, toxicology, and safety assessment of drugs. 4-30…”
Section: Introductionmentioning
confidence: 99%